Design of Exemplary Storybook 5 Apostles Ulul Azmi by Cikal Aksara for Children Aged 10-12 Years Old - Banon Gilang; Alessandra, Alessandra; Citra Kemala Putri (PT FORMOSA CENDEKIA GLOBAL, 2024)
Five Apostles are stand out among 25 Prophets of Islam for their extraordinary forbearance and perseverance in carrying out their responsibilities, and they are recognized with the honorific title of Ulul Azmi. Among these holy people are Noah, Moses, Abraham, Isa, and Muhammad. Children are usually introduced to these Prophets and Apostles through storytelling, storybooks are a popular medium for this purpose. Using a qualitative approach, this project highlights the significance of preserving a pleasing harmony between text, pictures, and colors. The goal of the design project is to produce an appropriate children's storybook called